Factors associated with the quality of life among river communities along Sungai Pahang and Sungai Muar, Malaysia - Ramli, Siti Aisyah (2014)
The purpose of this study was to examine the quality of life of river communities. Although the government has been championing efforts to keep rivers clean and environmentally sustainable but there are only certain to be known about the past and current impact of rivers onto the quality of life for those living near the rivers. The question to be answered is whether after several decades of economic development the quality of life of communities along the rivers has improved? The main objective of this study is to determine the quality of life among the river communities along Pahang and Muar river. Specifically, the objectives for this research are 1) To determine the level of quality of life among community living along the Pahang River and Muar River; 2) To compare the differences in dimension of quality of life by location, gender and level of education; 3) To determine the relationship between selected demographic factors and quality of life aspects; 4) To determine factors contributing towards the quality of life. This study involved 900 respondents who live within two km from the river from three areas which are Pekan, Bahau and Muar. This study was conducted using quantitative method. The questionnaire was developed from previous research instruments. At the pre-test (Pilot Test) stage, thirty respondents were selected and analysis showed that the instrument as reliable. To determine the quality of life of the respondents, researchers used SPSS version 20 for data analysis. Descriptive analysis was used to define the sociodemographics of respondents. Then to identify the difference and the relationship between the socio-demographic factors and the quality of life, t-test analysis, ANOVA and Pearson product-moment correlation was employed. Regression analysis was used to determine factors that contributed towards the quality of life among the river community. Findings showed that the quality of life among river community was at the moderate level. Analysis such as t-test indicated that there is a difference between socio-demographic factors (gender and education level) and the quality of life. However, there is no difference between location and quality of life. Based on the Pearson product-moment correlation and regression, monthly income and distance to the nearest river was shown to have associated with and contributed to the quality of life among river community along Pahang and Muar river. So, the government and local agencies need to cooperate and work together to improve policies and increase monitoring especially planning in managing, controlling,coordinating and strengthening the development of physical, social and economic area of the river to ensure a higher quality of life of river communities.